Dora the explorer. Pirate adventure - Conrad, Gary; Herles, Kathleen; Chad, Harrison (Hollywood, Calif. : Paramount, 2004)
Dora and friends stage a musical play about pirates.
Bonus episodes: Dora saves the prince -- El Coqui.
"Dora's first double-length musical episode"--Container.
Features: bonus "Oobi : the friend who's always with you," interactive features, scene access, interactive game, sing a pirate song game, interactive menus, karaoke, Dora's sing along flash cards.
Voices: Kathleen Herles, Harrison Chad, Marc Weiner.
MPAA rating: Not rated.
DVD, Dolby digital stereo.
Closed-captioned.
Keywords: Explorers -- Juvenile drama; Pirates -- Juvenile drama; Riddles -- Juvenile drama; Explorers -- Drama; Pirates -- Drama; Riddles -- Drama; Children's television programs